Accurate reconstruction of bone defects in orbital–maxillary–zygomatic (OMZ) complex with polyetheretherketone (PEEK). Issue 5 (May 2022) - Lv, Mingming; Yang, Xin; Gvetadze, Shalva R.; Gupta, Anand; Li, Jun; Sun, Jian
Summary: Purpose: The aim of this study was to evaluate the safety and efficacy of using patient-specific polyetheretherketone (PEEK) for the reconstruction of patients with defects in orbital–maxillary–zygomatic (OMZ) complex. Patients and Methods: This study included 12 patients who underwent primary/delayed reconstruction of defects in OMZ complex by using patient-specific PEEK implants. Postoperative appearance (facial and orbital symmetry) and function were assessed after 6 months. Ophthalmologic examinations including globe position, exophthalmos, and orbital volume measurement were also performed. A comparative analysis of the treatment outcomes between pre- and postoperation was performed, and a value of P < 0.05 was considered as significant. Results: All patients underwent planned surgical procedure successfully. No obvious complications occurred. Facial symmetry and globe position were improved after surgery and the postoperative esthetic assessment was rated as excellent. The postoperative evaluation revealed that exophthalmos was 15.91 ± 1.80 mm, vertical position difference of eyeball 15.91 ± 1.80 mm, and orbital volume 15.91 ± 1.80 mm, respectively. There was a statistically significant difference in the mean values of exophthalmos, vertical position difference, and orbital volume among pre- and postoperation conditions, whereas there was no statistically significant difference between the reconstructed side and the unaffected side after surgery. Conclusion: With the aid of virtual surgical planning and individual custom-made surgical guides, patient-specific PEEK implantation can successfully reconstruct the complicated 3D structure of OMZ complex and shows excellent biocompatibility and clinical outcomes.